ANALISIS KINERJA KEUANGAN KOPERASI SERBA USAHA ANTARA BERDASARKAN LAPORAN KEUANGAN TAHUN 2022 – 2024 - Rahman Rahman; Zelda Bintani Putri Rambe; Edo Fransiskus; Hadli Lidya Rikayana (Journal of Innovative and Creativity, 2025)
This study aims to analyze the financial performance of the ANTARA Multipurpose Cooperative based on its financial statements for the period 2022–2024. Financial performance analysis is conducted to assess the cooperative’s financial health and the effectiveness of financial management in supporting business sustainability. This research employs a descriptive quantitative method using a financial ratio analysis approach. The data used consist of the cooperative’s financial statements, including balance sheets and statements of remaining operating results during the research period. The analysis is conducted in accordance with the Guidelines for Outstanding Cooperative Assessment as stipulated in the Regulation of the Minister of Cooperatives and SMEs No. 06/Per/M.KUKM/V/2006, which include liquidity, solvency, and profitability ratios. The results indicate that the cooperative’s liquidity performance is classified as unhealthy, reflected by extremely high and fluctuating current and cash ratios, suggesting inefficiencies in managing current assets, particularly receivables and cash. In contrast, the solvency performance shows a healthy condition, as indicated by low debt levels relative to total assets and equity. From a profitability perspective, the cooperative demonstrates a fairly good performance, as shown by stable return on assets, although return on equity has declined, indicating suboptimal utilization of own capital. This study is expected to provide valuable insights for cooperative management in improving financial efficiency and formulating strategies for sustainable business development.